Visions and re-visions of community: Praxis and narratives of belonging (and un-belonging) among international students - Gatundu, Stephen (My University, 2026)
Apart from the practical challenges of learning (in) a new institution, when international students arrive at a new university, they face the deeper and more demanding challenge of making themselves understood – socially, emotionally, culturally, and even intellectually – in an environment that is not organized around their ways of being. Drawing on 19 in-depth interviews conducted in a university in the American Midwest, this qualitative study, employing narrative inquiry, explores how international students construct meaningful social ties within, through, and beyond the processes of integration that the institution and the local communities have in place; how they participate in everyday acts of connection, and, consequently, how their senses of community and belonging are impacted. At the heart of this study, I argue that as international students seek or build community, they engage in an ongoing, largely invisible form of labor: translation labor. Translation labor is the emotional and cognitive effort through and by which international students work to render themselves visible and legible across cultural grammars – adjusting how they speak, relate, and present themselves in order to be recognized and accepted. This study argues that recognition and acceptance are not incidental to belonging; they are its very foundation. To be accepted and recognized – to have one’s presence acknowledged as meaningful, one’s experiences from home as relevant, one’s difference received without penalty – is, in practice, to belong. Where recognition and acceptance are withheld or conditional and where the translation labor is hefty, belonging remains aspirational rather than lived. This study further advances the argument that, unlike formal freedom, felt/inhabited freedom – when international students can inhabit social spaces freely and without the labor of constant translation – is a precondition for both community and belonging.
Keywords: International students; Belonging; Translation labor; Community; Emotional labor